The possible responsiveness of FDI to electric power consumption at different income levels - Sigo, Wondimu Tekle (International Multidisciplinary Research Journal, 2022)
Modern energy in the form of electricity is vital for economic activities such as getting clean water, and healthcare, getting stable and effective lighting, heating, and cooking. However, in developing countries, there is a huge shortage of electricity and big gaps in access, while access to electricity in developed countries almost reached a hundred percent. Hence, the purpose of this paper is to show the possible responsiveness of FDI to electric power consumption at different income-level. Hence, this study aims to address questions, including how is the relationship between economic activities such as FDI and electricity consumption at different income-level. For motivating the research, 131 countries’ data have been collected from WDI and US-EIA from 1992 to 2016 and both quantitative and qualitative methods were used. The cross-country regression result shows that there exists an inverse-U shaped relationship between EPC and FDI net inflow because most high-income countries have a high level of EPC and therefore EPC becomes less important for them to attract FDI. But when we separate the total sample into two, EPC can significantly increase net FDI inflow for middle & low-income countries because for these countries, especially for low-income countries, sufficient electricity supply is important for FDI inflow.